Tumor-induced lymphangiogenesis in cervical lymph nodes in oral melanoma-bearing mice - Ozasa Ryuki (Journal of Experimental & Clinical Cancer Research, 2012)
Abstract Background Metastasis via the lymphatic system is promoted by lymphangiogenesis. Alterations of the lymphatic channels during the progression of metastasis to regional lymph nodes (LNs) remain unexplored. To examine whether tumor-induced LN lymphangiogenesis controls metastasis to regional LNs, we investigated cervical LN metastasis in a mouse model of oral melanoma. Methods Injection of B16F10 melanoma cells into mouse tongues replicated spontaneous cervical LN metastasis. We performed histological, immunofluorescent, and histomorphometric analyses of tumor-reactive lymphadenopathy and lymphangiogenesis in tumor-associated LNs. We investigated the expression of vascular endothelial growth factor (VEGF)-C and its receptor, VEGF receptor-3 (VEGFR-3), in tumor cells and tissues, and LNs by reverse transcription polymerase chain reaction and immunofluorescence. Results Tumor-associated LNs comprised sentinel LNs (SLNs) before and after tumor cell invasion (tumor-bearing SLNs), and LNs adjacent or contralateral to tumor-bearing SLNs. Extensive lymphangiogenesis appeared in SLNs before evidence of metastasis. After metastasis was established in SLNs, both LNs adjacent and contralateral to tumor-bearing SLNs demonstrated lymphangiogenesis. Interaction between VEGF-C-positive melanoma cells and VEGFR-3-positive lymphatic vessels was evident in tumor-associated LNs. Conclusions LN lymphangiogenesis contributes a progression of tumor metastasis from SLNs to other regional LNs.